Amphibians and reptiles associated with the prairie dog grasslands ecosystem and surrounding areas at the janos casas grandes complex, Northwestern Chihuahua, México - Santos-Barrera, Georgina; Pacheco, Jesús; Ceballos, Gerardo (Instituto de Ecología, A.C., 2008)
Prairie dogs (Cynomys ludovicianus) are considered a keystone species that forms extensive colonies in the grasslands of western and central North America. These colonies are characterized byhigh diversity of associated vertebrates. The largest colonies in North America are located in the Janos region, northwestern Chihuahua, Mexico. In this study we present an inventory of the amphibians and reptiles inhabiting at prairie dog grasslands and surrounding mesquite scrublands in the Janos region. Methods to assess the herpetofauna included the use of a combined system of pitfall traps and visual encounter surveys (VES). We found 9 species of amphibians and 35 of reptiles. Of these species, 28 were closely related to prairie dog colonies, and 18 were exclusively recorded in this habitat. Additionally, 13 species were restricted to the mesquite scrubland. The Janos amphibian and reptile communities are of conservation concern, because 16 of the included species (1 amphibian and 15 reptiles) are considered at some risk of extinction. The diversity of amphibians and reptiles in the Janos region is clearly high in comparison with other grasslands. Our results strongly support the assumption that prairie dog grasslands are important for maintaining the mammal and avian diversity in the ecosystems of the Chihuahuan desert.